Thermal, Mechanical and Rheological Properties of Agro Fiber Filled High Density Polyethylene Biocomposites - Ogah, Anselm O; Englund, Karl R (International Journal of Chemistry and Materials Research, 2016)
The thermal, mechanical and rheological properties of corncob, rice hull, walnut shell and flax shive agro-wastes/high density polyethylene bio-composites were studied. Results indicated that the fibers showed two and three mass loss steps due to moisture evaporation and decomposition of hemicelluloses, cellulose and lignin. The flax shive was thermally more stable and showed a decrease in activation energy with increase in conversion rate while the other three fibers showed increase in activation energy with conversion rate. The apparent activation energy values of the fibers was 161±11.06to200±4.69 kJ/mol. Particle size distribution of 60-100 mesh size of the fibers was 0.295 mm to ˂ 0.125 mm. The composites showed remarkable increases in flexural modulus and un-notched Izod impact strength and a decrease in flexural strength compared with the neat HDPE. The rice hull composite showed superior flexural strength of 22.5 MPa. The flax shive composite gave superior flexural modulus of 3.0 GPa and the walnut shell composite gave superior un-notched Izod impact strength of 52.5 J/m. The complex viscosities of all the composites decreased with increase in frequency. The corncob composite showed higher complex viscosity of 3,600,000 Pas. The walnut shell composite exhibited higher storage modulus of 800,000 GPa at low frequency but decreased with increase in frequency, whereas the other three fiber composites showed increased storage modulus with increase in frequency. Corncob composite showed superior loss modulus of 200,000 GPa. The damping factor of the composites decreased with increasing frequency with walnut shell composites exhibiting superior damping factor. The study has shown that the properties of the composites varied substantially based upon the type of agro fiber utilized.